2017
DOI: 10.1002/bit.26347
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic modeling of energy balances in Mycoplasma hyopneumoniae shows that pyruvate addition increases growth rate

Abstract: Mycoplasma hyopneumoniae is cultured on large‐scale to produce antigen for inactivated whole‐cell vaccines against respiratory disease in pigs. However, the fastidious nutrient requirements of this minimal bacterium and the low growth rate make it challenging to reach sufficient biomass yield for antigen production. In this study, we sequenced the genome of M. hyopneumoniae strain 11 and constructed a high quality constraint‐based genome‐scale metabolic model of 284 chemical reactions and 298 metabolites. We v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…There was also down-regulation in vivo of the operons related to myo-inositol and ribose transport and catabolism ( Figure 4 ). As the in vitro medium does not contain high levels of unbound myo-inositol ( Kamminga et al, 2017b ), up-regulation of this pathway under in vitro conditions can be expected. Another down-regulated operon is involved in oligopeptide transport.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was also down-regulation in vivo of the operons related to myo-inositol and ribose transport and catabolism ( Figure 4 ). As the in vitro medium does not contain high levels of unbound myo-inositol ( Kamminga et al, 2017b ), up-regulation of this pathway under in vitro conditions can be expected. Another down-regulated operon is involved in oligopeptide transport.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing of the library was done using the Illumina HiSeq 2500: single-end reads, 50 cycles. Quality assessment of reads was done as previously described ( Kamminga et al, 2017b ). Reads were aligned to the strain 98 genome using TopHat v2.1.0 ( Kim et al, 2013 ) with the standard settings for strand-specific alignment enabled (fr-firststrand).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the immunogenicity and biological characteristics of Mhp strains, the self-replicating plasmids with the origin of replication ( oriC ) sequences from Mhp could be useful genetic engineering vectors for strain improvement, which had expressed EGFP in Mhp cells successfully ( 85 , 101 ). On the other hand, genome-scale metabolic engineering techniques provided more information for the optimization of fermentation process, studies had reported that the addition of pyruvate could increase Mhp growth rate in special fermentation experiment ( 102 ).…”
Section: New Strategies For Next-generation Vaccines Development Agaimentioning
confidence: 99%
“…Design strategies vary based on the type of antigen that is needed ( Figure 1A). GEMs can be applied in this stage to predict the effect of using gene knockout or knock-in mutant strains with respect to optimal growth rates or antigen production [14]. Although not all bacterial pathogenic strains are considered to be genetically amenable, recent advances in gene editing techniques have considerably expanded the toolbox enabling researchers to make targeted gene deletions even in bacteria that were previously thought to be inaccessible [15,16].…”
Section: Glossarymentioning
confidence: 99%